Papaya Mealybug, Paracoccus marginatus Williams and Granara de Willink (Insecta: Hemiptera: Pseudococcidae) - Alison Walker; Marjorie Hoy; Dale Meyerdirk (EDIS)
The papaya mealybug, Paracoccus marginatus Williams and Granara de Willink, is a small hemipteran that attacks several genera of host plants, including economically important tropical fruits and ornamentals. The papaya mealybug was discovered in Manatee and Palm Beach counties in Florida in 1998 and subsequently spread rapidly to several other Florida counties. It potentially poses a multi-million dollar threat to numerous agricultural products in Florida, as well as other states, if not controlled. Biological control was identified as a key component in a management strategy for the papaya mealybug, and a classical biological control program was initiated as a joint effort between the US Department of Agriculture, Puerto Rico Department of Agriculture, and Ministry of Agriculture in the Dominican Republic in 1999. This document is EENY-302, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: August 2003.